The association between perceived social support and amygdala structure. (May 2016) - Sato, Wataru; Kochiyama, Takanori; Kubota, Yasutaka; Uono, Shota; Sawada, Reiko; Yoshimura, Sayaka; Toichi, Motomi
Abstract: The subjective perception of social support plays a crucial role in human well-being. However, its structural neural substrates remain unknown. We hypothesized that the amygdala, specifically its laterobasal and superficial subregions, which have been suggested to serve social functions, could be associated with the level of perceived social support. To test this hypothesis, we assessed perceived social support using the Multidimensional Scale of Perceived Social Support. In addition, we measured the volume and shape of the amygdala using structural magnetic resonance imaging in 49 healthy participants. Global amygdala volume in the left hemisphere was positively associated with the perceived social support score after adjusting for total cerebral volume, sex, age, intelligence, and five-factor personality domains. The local shape of the laterobasal and superficial subregions of the left amygdala showed the same association with perceived social support. These data suggest that the social subregions of the left amygdala are associated with the implementation of perceived social support. Highlights: We assessed perceived social support. We also measured the volume and shape of the amygdala using structural MRI. Left amygdala volume was positively associated with perceived social support. The association was identified at the laterobasal and superficial subregions.